Factors Influencing Customer Satisfaction: Empirical Study at Bank Muamalat Madiun Branch - Puspitasari, Rinda Eka; Nisak, Khoirun (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: Customer satisfaction aims to create, rectify, and maintain customers' loyalty towards a bank and its products. When customers feel satisfied, they are more likely to repeat purchases with the bank and recommend them to others. Research Methods: This study aims to determine whether excellent service, product quality, and complaints handling influence customer satisfaction at Bank Muamalat Madiun Branch. The research employs a quantitative approach, utilizing primary data collected through questionnaires distributed to 100 respondents, a sample from the total population of 8,920 savings account holders at Bank Muamalat Madiun Branch. Hypothesis testing is conducted using multiple regression analysis with the assistance of SPSS 21 for Windows. Results: The findings reveal that excellent service, product quality, and complaints handling positively and significantly impact customer satisfaction at Bank Muamalat Madiun Branch. This supports the assumption that satisfied customers are more likely to engage in repeat transactions and recommend the bank to others. Conclusion: The implications of this research can serve as a strategic foundation for Bank Muamalat to enhance its services, product quality, and customer complaint resolution, fostering customer satisfaction and supporting sustained long-term growth.